An Assessment of the Differential Calculus Textbook from the perspective of Faculty Members - Kandeel, Refat A. A. (Advances in Social Sciences Research Journal, 2018)
The purpose of this study was to assess the Differential Calculus textbook for the Common First Year students at King Saud University from perspective of faculty members. The study sample consisted of 27 faculty members. The researcher prepared a questionnaire to assess the Differential Calculus Textbook. It consisted of four sections (introduction, method of presentation, content, and output). The study results indicated that the Differential Calculus textbook was medium level. The output textbook was the largest assessment, followed by the introduction, while the method of presentation was in the last ranking, preceded by the content. The method of presentation and content are very important when writing any textbook, so these two sections needed careful review, and continuous development and improvement based on the results of this study.